The problem of translating the cultural dimension in legal acts: Act of habous as a model - Ghedir, Sonia; Chenni, Fairouz (Journal of Human Sciences, 2023)
The quality of translation is closely linked to translator’s level and culture. Moreover, texts which are characterized by cultural aspect constitute many constraints for translators. That’s what we wanted to highlight, especially with regard to legal texts, which are covered with law language and bearing various cultural aspects. We will discuss, through this paper, the problem of transferring cultural aspect of legal acts, taking as a model "Act of habous" translated by Mohamed Tiar. We will then wonder about the success of the translating operation and about the transfer of all cultural, religious and social specifities into the French language? In order to well understand this problem, we opted for an analytical and critical method and we thought suitable to start this article with theoretical notions relating to it, to arrive at the corpus and translation analysis.